2019
DOI: 10.1161/jaha.118.010456
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of MicroRNA‐206 Inhibits Potassium Voltage‐Gated Channel Subfamily A Member 5 in Pulmonary Arterial Smooth Muscle Cells and Is Related to Exaggerated Pulmonary Artery Hypertension Following Intrauterine Growth Retardation in Rats

Abstract: Background Intrauterine growth retardation ( IUGR ) is related to pulmonary artery hypertension in adults, and mi croRNA ‐206 (miR‐206) is proposed to affect the proliferation and apoptosis of pulmonary artery smooth muscle cells ( PASMC s) via post‐transcriptional regulation. Methods and Results In an IUGR rat model, we found that the expression and function of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…However, the exact mechanisms by which K + channels act on PASMC are still controversial [ 41 51 ]. Lv et al found increased expression of MicroRNA-206 suppressed potassium voltage-gated channel subfamily A member 5 (Kv1.5) and promoted the PASMC proliferation [ 52 ].…”
Section: Possible Pathways To Act On Pasmcmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exact mechanisms by which K + channels act on PASMC are still controversial [ 41 51 ]. Lv et al found increased expression of MicroRNA-206 suppressed potassium voltage-gated channel subfamily A member 5 (Kv1.5) and promoted the PASMC proliferation [ 52 ].…”
Section: Possible Pathways To Act On Pasmcmentioning
confidence: 99%
“…However, the exact mechanisms by which K + channels act on PASMC are still controversial[41][42][43][44][45][46][47][48][49][50][51]. Lv et al found increased expression of MicroRNA-206 suppressed potassium voltage-gated channel subfamily A member 5 (Kv1.5) and promoted the PASMC proliferation[52].e elevated concentration of intracellular Ca 2+ was found in PAH animal models and patients.is kind of phenomenon was not realized through activation of voltagegated calcium channels (VGCC), but by increase of canonical transient receptor potential (TRPC) proteins, which involved Ca 2+ -permeable nonselective cation channels (NSCCs). Increased abundance of NSCCs was detected in PAH rat models and patients and inhibition of NSCCs, either pharmacologically or by RNA silencing, effectively decreased the concentration of intracellular Ca 2+ and proliferation of PASMC[53][54][55][56][57][58][59][60][61].…”
mentioning
confidence: 99%
“…7678 Other factors that regulate cell proliferation, such as microRNA and mitogen, also regulate cell proliferation by down-regulating the expression of Kv1.5. 79,80 Kv channel can not only promote cell proliferation, but also inhibit apoptosis. It has been found that after inhibiting the anti-apoptotic protein Survivin, the expression of Kv1.5 and Kv2.1 was up-regulated, and the apoptosis of PASMCs was promoted in the model of PH.…”
Section: Introductionmentioning
confidence: 99%
“…Transient transfection of a Kv channel or a K + channel activator increases K + efflux to enhance PASMC death [ 45 , 46 ]. The decrease of K + channel expression, such as Kv1.5 and Kv1.2, leads to the proliferation of PASMCs [ 47 ]. The opening of potassium channels promotes cell membrane hyperpolarization and reduces calcium overload.…”
Section: Discussionmentioning
confidence: 99%